INTEGRASI PENDIDIKAN AGAMA DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK: A SYSTEMATIC LITERATURE REVIEW - A’zizah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2026)
This study aims to examine the integration of religious education in shaping students’ character through a Systematic Literature Review (SLR) approach. This method is used to identify, evaluate, and synthesize relevant studies systematically. The findings indicate that religious education plays a significant role as a source of moral and spiritual values in character formation. The integration of religious and character education can be implemented through various strategies, including curriculum integration, teacher role modeling, value habituation, interdisciplinary approaches, and strengthening school culture and social environments. A holistic and contextual approach is found to be more effective in internalizing character values into students’ daily behavior. However, its implementation still faces several challenges, such as the dominance of cognitive-oriented learning, limited teacher competence, and the influence of globalization and digital technology. Therefore, it is necessary to develop adaptive, innovative, and context-relevant integration models.